Seafloor Geodesy From Repeated Multibeam Bathymetric Surveys: Application to Seafloor Displacement Caused by the 2011 Tohoku-Oki Earthquake - Fujiwara, Toshiya (Frontiers in Earth Science, 2021)
Repeated multibeam bathymetric surveys played an important role for understanding the distribution of coseismic seafloor displacement caused by the 11 March 2011 Mw 9.0 Tohoku-oki earthquake. After the earthquake, we collected bathymetric data along the same tracks obtained before the earthquake. The selected tracks were crossing the trench and extending from the landward to seaward trench slopes. We examined the seafloor displacement on the landward relative to the seaward by means of the difference in bathymetry before and after the earthquake. The multibeam bathymetric survey has an advantage of areal coverage. The repeated surveys clarified the areal distribution of the coseismic seafloor displacement. In the main rupture area, very large seafloor displacement was observed. Sharp bathymetric change at the trench axis provided solid evidence that the fault slip on the shallowest part of the megathrust reached the trench axis and peaked at the trench axis. The very large displacement is limited to the particular area. Smaller seafloor displacements were observed in the area tens of kilometers away from the main rupture area. We present methods and results of the repeated multibeam bathymetric surveys and an application to the seafloor displacement caused by the 2011 Tohoku-oki earthquake in the northern Japan Trench. Less than several meters in seafloor vertical displacements and less than 20 m in seafloor horizontal displacement were estimated in the northern Japan Trench. The estimated smaller displacements are comparable in magnitude to error of the seafloor displacement observation from our bathymetric survey. Nevertheless, adjacent three survey tracks showed coherent relative differences in seafloor elevation along the survey tracks, which suggests the relative difference enables us to discuss the along-track variation in seafloor displacement in the area. However, our survey was affected by uncertainties of roll and pitch biases and sound velocity errors. Well-prepared repeated multibeam bathymetric survey for the purpose of seafloor geodesy could lead to a higher resolution and more accurate result. Repeated acquisition of high resolution and accuracy bathymetric data using state-of-the-art technology will be important to quantitative discussion of the seafloor displacements caused by even smaller magnitude earthquakes and tsunamis.